Fudge bites - Coco, Nancy (Coco, Nancy. Candy-coated mystery., 2019)
"Halloween on Mackinac Island is a season of fun tricks, but finding a corpse is no treat for fudge shop owner Allie McMurphy."--Page 4 of cover